1997
DOI: 10.1002/(sici)1096-8652(199712)56:4<244::aid-ajh8>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperthermal stress on the ultrastructure of platelets with reference to the localization of platelet peroxidase and fibrinogen in vivo

Abstract: Ultrastructure of platelets with the localization of platelet peroxidase and fibrinogen through 3-min 47 degrees C hot-spring bathing was investigated in eight healthy volunteers. The mean sublingual temperature rose about 1.8 degrees C 5 min after the start of bathing. The frequencies of fold, pseudopods, vacuoles, and centralization were increased after bathing. Platelet peroxidase activity was decreased after bathing. Furthermore, fibrinogen was decreased in alpha-granules after bathing. Thus, hyperthermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…These studies examined the effects of hyperthermal stress on platelets and found partial platelet activation after a 3-min hot-spring bath 18 or platelet aggregation and activation after platelet incubation at 43°C. 19 Therefore, it was our hypothesis that heat could play another central role in activation of PRP by calcium sulfate.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies examined the effects of hyperthermal stress on platelets and found partial platelet activation after a 3-min hot-spring bath 18 or platelet aggregation and activation after platelet incubation at 43°C. 19 Therefore, it was our hypothesis that heat could play another central role in activation of PRP by calcium sulfate.…”
Section: Figmentioning
confidence: 99%
“…It has been reported that heat can act as a weak agonist in platelet activation. 18,19 On activation, the platelet dense bodies, the most rapidly secreted of platelet organelles, release ADP, as well as ATP and serotonin. The a granules release platelet-derived growth factor (PDGF), transforming growth factor b 1 (TGF-b 1 , connective tissue activating peptide III (CATP III), thrombospondin, factor V, fibrinogen, factor XI, plasminogen activator inhibitor 1 (PAI-1), and adhesive proteins such as fibrinogen, fibronectin, von Willebrand factor (vWF), and P-selectin (also called GMP-140, structurally similar to E-and L-selectins).…”
Section: Introductionmentioning
confidence: 99%